(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2013)
The present study developed and validated an HPLC method for the simultaneous determination of artesunate (AS) and mefloquine hydrochloride (MQ) in fixed-dose combination tablets, according to ICH guidelines. The chromatographic separation was carried out on an XBridge C18 (250 x 4.6 mm i.d., 5 µm particle size, Waters) analytical column. The mobile phase included a 0.05 M monobasic potassium phosphate buffer (pH adjusted to 3.0 with phosphoric acid) and acetonitrile (50 + 50, v/v). The flow rate was 1.0 mL/min, and the run time was 13 minutes. A dual-wavelength approach was employed: AS detection was performed at 210 nm and MQ was detected at 283 nm, using a diode array detector. Stability of sample solutions was evaluated for 8 hours after preparation, during which time the solutions remained stable. Youden's test was employed to evaluate robustness. The method proved to be linear (r²>;0.99), precise (RSD